Evaluación de tratamientos naturales con cúrcuma y tomillo para el control de saprolegniasis en trucha arcoíris (oncorhynchus mykiss) en la comunidad de coyoctor. - Serpa Padilla, Edison Adrián (2025)
This study addresses the efficacy of turmeric and thyme treatments for the control of saprolegniasis in trout. The main objectives were: i) To determine the time intervals for the effects of natural treatments in controlling saprolegniasis. ii) To establish the clinical signs of alterations caused by saprolegniasis. iii) To verify the effectiveness of the natural treatments applied to rainbow trout. The methodology used was an experimental design with three treatments: turmeric, thyme, and a control group. The treatments were administered over a determined period, and subsequently, the prevalence of the disease, mortality, and morbidity rates in the trout were evaluated using descriptive analysis. This analysis described and summarized the characteristics of the collected data, employing measures of central tendency and dispersion, such as frequencies and percentages. The results highlight that T2 (50 trout + 200g of macerated turmeric in 20L of H2O) was the most effective, achieving significant prevention of saprolegniasis, whereas T1 (control group) and T3 (50 trout + 200g of macerated thyme in 20L of H2O) showed no positive effects. The main conclusion is that the T2 formulation provides prolonged and effective protection against saprolegniasis, making it a viable option for aquaculture. It is recommended to extend the studies to other aquatic species to evaluate the efficacy of these findings, conducting long-term research to monitor the treatments’ effects and analyze their environmental impact to ensure sustainable application. Finally, T2 demonstrated an 80% success rate in preventing saprolegniasis within 20 days. Therefore, this treatment is recommended for implementation in aquaculture systems, considering its feasibility in controlling the disease in rainbow trout. Additionally, cost studies are suggested to ensure the economic sustainability of its application.